Let the whole earth sing praise - DePaola, Tomie, 1934-2020. (New York : G. P. Putnam's Sons, 2011)
With text inspired by Old Testament Scripture and artwork fashioned after the beautiful embroideries and designs of the Otomi people from the mountain villages around San Pablito, in Puebla, Mexico, this is a wonderful celebration for all to share.
004-008.
Elementary Grade
Keywords: Creation -- Biblical teaching -- Juvenile literature; Creation -- Pictorial works -- Juvenile literature; Creation